Parents’ awareness and practice of COVID-19 health protocols: Basis for glocalized IEC material development - Nagal, Raphael Kevin; Ningal, Mary June; Invina, Joanna Grace (Indonesian Journal of Education and Pedagogy, 2025)
The COVID-19 pandemic emphasized the critical role of parents in ensuring accurate health information and consistent preventive practices at home. This study assessed parents’ awareness of key COVID-19 facts and the extent to which they adhered to recommended health protocols, serving as the basis for developing a glocalized information, education, and communication (IEC) material. Using a design research approach guided by Stanford University’s Design Thinking Model, the study surveyed 1,200 parents in Aklan, Philippines, and consulted experts in IEC development. Results showed that parents were generally aware of COVID-19 health facts (M=3.03) and exhibited a moderate level of protocol adherence (M=3.15). Awareness was lowest for vaccination-related information, influenced by past vaccine controversies and inconsistent public communication. A strong positive correlation (r=0.807, p<0.001) indicated that higher awareness was associated with better adherence. Based on these findings, a culturally contextualized trifold pamphlet integrating local language, familiar visuals, and community-relevant guidelines was developed and evaluated. Parents and experts rated the material as highly acceptable (M=3.71), citing its clarity, cultural fit, and practical usefulness. While the IEC resource shows promise for supporting community health education, further studies are needed to determine its long-term influence on behavior and pandemic preparedness.